Telehealth use in rural and remote health practitioner education: an integrative review - Pauline Calleja; Susan Wilkes; Melinda Spencer; Steven Woodbridge (James Cook University, 2022)
Introduction: For rural and remote clinicians, quality education is often difficult to access because of geographic isolation, travel, time, expense constraints and lack of an onsite educator. The aims of this integrative review were to examine what telehealth education is available to rural practitioners, evaluate the existence and characteristics of telehealth education for rural staff, evaluate current telehealth education models, establish the quality of education provided through telehealth along with the facilitators or enablers of a successful service and develop recommendations for supporting and developing an education model for rural and remote health practitioners through telehealth. Methods: An integrative review was conducted following the five-stage integrative review process. Searches were conducted in the electronic databases CINAHL, Medline, Nursing & Allied Health (Proquest), PubMed, Johanna Briggs Institute Evidence Based Practice (JBI EBP) and Embase. Results: Initial searches revealed more than 7000 articles; final inclusion and exclusion criteria refined results to 60 articles to be included in this review. Included articles were original research, case studies, reviews or randomised controlled studies. Countries of origin were countries in North and Central America, the UK, Europe, and Africa, and Australia and India. One issue noted with this review was classifying rural and remote; contexts used included rural, remote, regional, isolated, peripheral, native communities and outer regional or inner regional. Sample sizes in the studies ranged from 20 to more than 1000 participants, covering a broad range of health education topics. Delivery was mostly by a didactic approach and case presentations. Some included a mix of videoconferencing with face-to-face sessions. Overall, telehealth education was well received, with participants reporting mostly positive outcomes as signified by feeling less isolated and more supported. One interesting result was that quality in telehealth education is poorly established as there appears to be no definitions or consensus on what constitutes quality in the delivery of telehealth education. Very few studies formally tested increase in skill or knowledge, which is usual with professional development programs that do not result in further qualifications. For those that did assess these, formal knowledge and skills assessment indicated that telehealth using videoconferencing is comparable to face-to-face training with significant benefits related to travel reduction and therefore cost. Recommendations were difficult to synthesise because of the broad issues uncovered and lack of quality in many of the studies. Conclusion: The applications for telehealth are still evolving, with some applications having poor evidence to support use. Overall, telehealth education is well received and supported, with positives far outweighing negatives. Anything that can improve connection with a community and decrease isolation experienced by rural clinicians can only be beneficial. However, further planning and evaluation of the quality of delivery of telehealth education and addressing how education outcomes can be measured needs to be addressed in this widely growing area of telehealth.